Fula Ordboken - Dagrin, Bengt (University of Gothenburg, 2025)
Words from https://www.fulaordboken.se/

Ord från https://www.fulaordboken.se/
Fula Ordboken
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik